Karakterisasi Morfologi dan Skrining Fitokimia Ekstrak Umbi dan Daun Tumbuhan Ginseng (Phytolacca octandra L.) - Intan Sari; Henri Henri; Eka Sari; Suharyanto Suharyanto (Al-Hayat: Journal of Biology and Applied Biology, 2021)
Ginseng plant (Phytolacca octandra L.) is a wild plant that has the potential to be used as medicine. The morphological characteristics of ginseng plants in Indonesia are different. Therefore, it is necessary to carry out research aimed at characterizing the morphology and phytochemical screening of ginseng (P. octandra L.) leaves and tubers. The research was conducted first by observing morphological characters and screening phytochemical compounds such as alkaloid test, flavonoid test, phenol test, tannin test, saponin test, terpenoid test, and steroid test. The results of the research on the morphological characterization of ginseng (P. octandra L.) were: having a taproot which was modified into a tuber, a round, smooth, red color, pointed leaf shape, the base and tip of the leaf were pointed, buni fruit type, round flat, colored blackish-purple when ripe, a compound flower is located at the end of the branch and has flat, round seeds. Ginseng tubers have triterpenoid and saponin compounds, while the leaves only have saponin compounds. The potential development of ginseng (P. octandra L.) is currently limited as traditional medicine by local people. This is due to limited knowledge in its development efforts and unknown phytochemical content.